2009
DOI: 10.1177/0269216309106980
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying the impact of standardized assessment and symptom management tools on symptoms associated with cancer-induced anorexia cachexia syndrome

Abstract: The objective of this study was to quantify the impact of standardized assessment and management tools on patient symptom scores in cancer-induced anorexia cachexia syndrome (ACS) using a within-group study design. Baseline assessments included the Patient Generated Subjective Global Assessment (PG-SGA) tool and an amended Symptoms and Concerns Checklist (SCC). Symptom management strategies, written for this project, were instigated. Follow-up SCC scores were collected at 2 and 4 weeks. Forty out of 79 patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0
9

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 15 publications
0
18
0
9
Order By: Relevance
“…Of all reported symptoms by the PG‐SGA in our study, only xerostomia was associated with reduced survival. Other studies have shown that xerostomia is quite prevalent and is 1 of the most distressing symptoms reported by patients with cancer, 28 , 29 as well as being a prognostic factor in advanced cancer 7 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Of all reported symptoms by the PG‐SGA in our study, only xerostomia was associated with reduced survival. Other studies have shown that xerostomia is quite prevalent and is 1 of the most distressing symptoms reported by patients with cancer, 28 , 29 as well as being a prognostic factor in advanced cancer 7 …”
Section: Discussionmentioning
confidence: 99%
“…For patients with a shorter expectation of survival, nutrition counseling should be considered to alleviate symptoms and the burden of the disease. For example, predominant interventions for xerostomia involve dietary advice and improvement of active mouth care, prescription of artificial saliva, mouthwash, and so on 29 . On the other hand, in patients with a longer expectation of survival, nutrition interventions aim at improving nutrition aspects, including the maintenance or improvement of nutrition status, body weight stabilization, adequate food intake, and improvement of quality of life 11 , 12 …”
Section: Discussionmentioning
confidence: 99%
“…Although there has been relatively few studies in this area, previous research indicates that many professionals find managing cachexia in patients with advanced cancer challenging [17, 22, 23]. Qualitative research carried out in the UK found that healthcare professionals’ professional practice was influenced by a combination of their existing knowledge, the culture within their clinical area and the availability of resources; variation in these areas contributed to inconsistent and potentially sub-optimal care [14, 15, 17].…”
Section: Discussionmentioning
confidence: 99%
“…A small prospective study assessing symptom burden demonstrated that the number of symptoms reported could be reduced by a standardized assessment and symptom management tool comprising nutritional and pharmacological interventions in patients with advanced cancers [31]. A small prospective study assessing symptom burden demonstrated that the number of symptoms reported could be reduced by a standardized assessment and symptom management tool comprising nutritional and pharmacological interventions in patients with advanced cancers [31].…”
Section: The Impact Of Symptoms On Nutritional Statusmentioning
confidence: 99%